Overcoming Adversity and Challenging Ethnocentric Perceptions: An Ethnographic Case Study of Traditional Malay Boat Making in Terengganu (KEMANUSIAAN The Asian Journal of Humanities, 2023)
This article examines the fate of Malay traditional boats and their craftsmen in the face of adversity in the new millennium. The Malays have a rich history of boatmaking, dating back to the days of the imperial Han dynasty when Malay, Indonesian and Indian ships dominated the trade between India and China. Among these were the Malay ships, which were recognised as enormous, ocean-going boats that won the Chinese adoration. During the Han period, Chinese warships adopted the ingenious sail-making method of Malay seafarers. However, as time passed and technology took hold, Malay boat building, like many other forms of traditional knowledge and expertise, declined. According to this study, Malay boat making represents a rich storehouse of unique Malay cultural practises. Paradoxically, existing scholarship on the subject often adopts a Westerncentric ethnocentric perspective, marginalising the craft and its craftsmen while imposing foreign worldviews upon them. This unintentional epistemological adversity, to some extent, poses a significant threat to the preservation of this endangered local Malay craft and the invaluable cultural heritage it represents. Through an ethnographic case study, this research aims to challenge ethnocentric perceptions, particularly Western by examining the construction techniques, cultural perspectives and unique elements of traditional Malay boat making in Terengganu. By comprehending and documenting this invaluable cultural heritage amid adversity, we contribute to the preservation and appreciation of Malay craftsmanship and indigenous knowledge.